Knowledge Sharing between Multinational Corporation’s Headquarters and Subsidiaries: the Impact of Manager’s Role, Compensation System and Cultural Differences - Halim, Nik Ab (Journal of Economics and Behavioral Studies, 2013)
Knowledge sharing is a systematic process for creating, acquiring, synthesizing, learning, sharing and using knowledge to achieve organizational goals. It is also a source of competitive advantage especially for multinational companies. The objective of this paper is to discuss the impact of subsidiary manager’s role in knowledge sharing, manager’s compensation system, and the level of cultural differences between home and host country on the level of knowledge sharing between the headquarters and subsidiaries of multinational companies. A study has been conducted at a subsidiary of a large manufacturing company in Malaysia. Data were collected via self-administered survey questionnaire. The respondents consist of 100 executives and managers of the company, and all the questionnaires distributed were filled and returned back for data analysis. Findings indicate that all three factors significantly influence the level of knowledge sharing with the manager’s compensation system has the strongest impact. MNC therefore should clearly define the manager’s role in knowledge sharing and provide attractive rewards and remunerations to encourage knowledge sharing. At the same time, cultural differences should not be considered as a barrier to knowledge sharing as this study indicates that it can be a driver for effective knowledge sharing between headquarters and subsidiaries.